Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Siswa Tunagrahita Kelas XI di Sekolah Luar Biasa (SLB) Negeri Sukapura, Kecamatan Kiaracondong, Kota Bandung pada Pembelajaran IPA - Luthfiyatulqolbiyah Nuryaman; Naswa Safinah; Ninda Nur Aidah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the impact of the Problem Based Learning (PBL) model on the learning outcomes of intellectually disabled 11th-grade students at SLB Negeri Sukapura, Kiaracondong District, Bandung City, in science subjects. The study involved two students with IQ ranges between 40-67. A collaborative approach was used, involving researchers and teachers to observe students' activities during problem-based learning sessions. Data were collected through observations, interviews, and learning outcome tests. The results indicated that implementing PBL positively influenced students' engagement and understanding, particularly among students with higher IQs. However, challenges persisted for students with lower IQs, requiring adjusted teaching methods for greater effectiveness. The application of PBL demonstrated an average improvement in learning outcomes, although some students did not meet the minimum mastery criteria. This study suggests further enhancements in the implementation of PBL to optimize learning experiences for intellectually disabled students.